محاضرات: الاتصال وتسيير الأزمة - عبد الحميد, بلعباس (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2023)
الهدف من هذه المطبوعة البيداغوجيا هو تمكين الطالب من التعرف على أهمیةاتصالالأزمةوالدورا الفعال الذي تعلبه في معرفة مراحل الأزمةأوالكارثةإلىغایةإدارتهاوالتحكمفیهاواسترجاعطبیعةالنشاط،ومدىمساهمتهفي عملیاتالتنظیموالتخطیطلإدارةالأزماتبفاعلیةواحترافية،خاصةبعدالدروسالمستفادمنهاأثناء إدارةلأزماتوكوارثمشابهةأومماثلة،ویضلهذا الموضوعمتشعبالمجالاتوالتخصصاتیستدعيجهوداضخمة،ووقتا مستفیضالتغطیةجمیعجوانبه. ومنبینالفروعالهامةفيمجالإدارةالأزماتمایتعلقبكیفیةإدارتهاعلىمستوىالجمهورالداخلي والجمهورالعامووسائلالإعلاموهومایعرفباتصالاتالأزمة،لذلكأردنا من خلال هذه المحاضرات إبراز الدور الفعالللجمهورمنخلالوسائلالإعلامووسائلالاتصالالأخرىمما یؤديحتماإلىنتائجایجابیةوملموسة عندإدارةأيأزمة . لقدباتمنالضروريالعملعلىإدارةالأزمةونذكرأنأولبدایةللتفكیرفيإدارتهاكانتمعأزمة الصواریخالكوبیةعام1962 ،ومنهذاالمنطلقأصبحینظرللأزمةلیسفقطكحالةطارئةومفاجئة ینتجعنهاأوضاعالا توازنوالاستقرارفيالنظموالقیم،إنماكفرصةللتغییروالتطویر،ویكونذلك منخلالتدخلالإنسانلتسییرهابطریقةعقلانیةورشیدةلإدارتها،وإنكانتالبدایةالفعلیةلهذهالعملیة قدظهرتعلىمستوىالعلاقاتالدولیةفإنإدارةالأزماتأصبحتكذلكتعنيالمؤسساتبمختلفأنواعها وخصائصها The aim of this pedagogical publication is to enable the student to recognize the importance of crisis communication and the effective role it plays in knowing the stages of a crisis or disaster in order to manage and control it and to recall the nature of the activity and the extent of its contribution to the processes of organizing and planning to manage crises effectively and professionally, especially after lessons. What can be learned from it during the management of similar or similar crises and disasters? This topic remains diverse in fields and specializations, requiring huge efforts and extensive time to cover all its aspects. Among the important branches in the field of crisis management is what is related to how to manage it at the level of the internal public, the general public, and the media, which is known as crisis communications. Therefore, through these lectures, we wanted to highlight the effective role of the public through the media and other means of communication, which inevitably leads to... Positive and tangible results when managing any crisis. It has become necessary to work on managing the crisis, and we remember that the first beginning of thinking about managing it was with the Cuban missile crisis in 1962. From this standpoint, the crisis has come to be viewed not only as an emergency and sudden situation that results in conditions of imbalance and stability in systems and values, but rather As an opportunity for change and development, this is through human intervention to manage it in a rational and rational manner. Although the actual beginning of this process has appeared at the level of international relations, then crisis management has also come to mean institutions of various types and characteristics.
Keywords: الأزمة ، التسيير ، الإدارة ، وسائل الإعلام ، المصطلحات المرادفة للأزمة : crisis, management, management, media, terms synonymous with crisis